Preferential Crystallographic Orientation and Optical Properties in (Ag,Zn)-Based Oxide Nanoparticle Thin Film Depending on Spark Voltage - Ebru Güngör; Tayyar Güngör (Nanomaterials and Nanotechnology)
The effect of spark voltage on nanoparticle (NP) formation, crystal structure, and optical properties of Zn and Ag-containing metal oxides produced using the spark-discharge (SD) technique was investigated. Quasispherical-shaped nanocrystals were observed in ZnO, Ag:ZnO, and AgO NP samples prepared at different spark voltages. The NP sizes in ZnO and Ag:ZnO samples were close and decreased as the spark voltage increased. It was observed that when AgO was prepared with only low-spark voltage (4.3 kV), tetrahedron/octahedron-shaped NPs were also formed. 4.3 kV spark voltage increased the crystal growth rate in the (100)-plane and 7 kV spark voltage also increased the crystal growth in the (002)-plane in hexagonal wurtzite ZnO and Ag:ZnO samples. Therefore, the a-axial preferred orientation of these samples at low-spark voltage had switched to the c-axial preferred orientation at high-spark voltage. For AgO, the increase in spark voltage revealed the monoclinic structure more strongly. The film thicknesses of AgO samples were close to each other with both spark voltages. Although, it was determined that the AgO prepared with 7 kV was optically more transparent and its optical band gap was significantly widened. This case may be due to the more presence of dodecahedral-shaped particles in the morphology of the AgO sample prepared. Therefore, the wider optical band gap of metal oxides decorated with such nanoparticles could indicate facet dependency. In addition, the film thickness and optical band gap of both ZnO and Ag:ZnO samples increased significantly depending on the increase of spark voltage. The optical band gap narrowed (redshifted) due to the effect of Ag ions entering the ZnO structure. As the spark voltage increased, the difference between the optical band gaps of ZnO and Ag:ZnO also increased. With the spark-voltage effect, the change in preferential crystallographic orientations of ZnO and Ag:ZnO samples and the change in optical band gap depending on the NP shape of the AgO sample can offer significant advantages in terms of optoelectronics.